The Effect of STAD-Cooperative Learning Model with Concept Maps in Promoting Students’ Self-Efficacy and Conceptual Understanding of Thermochemistry - Sani, Ida Nurjelita; Arianingrum, Retno (Universitas Pendidikan Ganesha, 2024)
The research sought to explore how employing the Student Team Achievement Division (STAD) cooperative learning model, along with concept maps, impacts the enhancement of students' self-efficacy and grasp of thermochemistry concepts. This study employed a quasi-experimental approach using a pretest-posttest control group design. It was carried out among 127 11th-grade science students from MAN 1 Bengkulu City, chosen through cluster random sampling. The information was gathered by utilizing self-efficacy questionnaires and conceptual understanding tests and was analyzed using Multivariate Analysis of Variance (MANOVA). The findings indicated that the obtained p-value was less than 0.05 (p<0.05), revealing a statistically significant difference in self-efficacy and conceptual understanding between students in the experimental and control groups. This suggests that students in the experimental group showed greater enhancements in self-efficacy and conceptual understanding when compared to those in the controlled group. Thus, These findings revealed that STAD-cooperative learning with concept maps had a better influence in enhancing self-efficacy and student conceptual understanding of thermochemistry.